2021
DOI: 10.1126/sciadv.abe0384
|View full text |Cite
|
Sign up to set email alerts
|

Exonuclease VII repairs quinolone-induced damage by resolving DNA gyrase cleavage complexes

Abstract: The widely used quinolone antibiotics act by trapping prokaryotic type IIA topoisomerases, resulting in irreversible topoisomerase cleavage complexes (TOPcc). Whereas the excision repair pathways of TOPcc in eukaryotes have been extensively studied, it is not known whether equivalent repair pathways for prokaryotic TOPcc exist. By combining genetic, biochemical, and molecular biology approaches, we demonstrate that exonuclease VII (ExoVII) excises quinolone-induced trapped DNA gyrase, an essential prokaryotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…This finding would suggest the other mode of mechanisms may also confer a high resistance but at a very low rate. 8 In terms of antibiotic susceptibility profile, all the QR ESBL-E. coli isolates were also MDR bacteria. These pathogens, however, were susceptible to carbapenems despite the low level of resistance (0.7%) to ertapenem (a member of carbapenems).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding would suggest the other mode of mechanisms may also confer a high resistance but at a very low rate. 8 In terms of antibiotic susceptibility profile, all the QR ESBL-E. coli isolates were also MDR bacteria. These pathogens, however, were susceptible to carbapenems despite the low level of resistance (0.7%) to ertapenem (a member of carbapenems).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, changes such as single nucleotide mutation of the genes may confer resistance to quinolone drugs by the bacterial cells. 8,9 Genetic mechanisms of quinolone resistance may also be mediated by plasmid bearing one or multiple genes such as qnrA, qnrB, and qnrC. 10 These genes encode for proteins that protect DNA gyrase and topoisomerase IV from quinolone inhibition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In eukaryotic cells, pathways exist for the removal of the covalently bound topoisomerase II enzyme and exposure of the DNA lesion to regular DNA repair mechanisms (Pommier, Huang et al 2014). In bacterial cells such pathways are not well known (but see (Huang, Michaels et al 2021)).…”
Section: Introductionmentioning
confidence: 99%
“…In eukaryotic cells, pathways exist for the removal of the covalently bound topoisomerase II enzyme and exposure of the DNA lesion to regular DNA repair mechanisms (Pommier, Huang et al 2014). In bacterial cells such pathways are not well known (but see (Huang, Michaels et al 2021)). Some work has also suggested that in Escherichia coli cleavage complexes can induce illegitimate recombination between two DNA segments (Ikeda, Moriya et al 1981, Ikeda 1994, Ikeda, Shiraishi et al 2004).…”
Section: Introductionmentioning
confidence: 99%